THE AXIOM OF SUSTAINABLE DEVELOPMENT - Cantú Martínez, Pedro César (2013)
The historical construction of the relationship between nature and humans, highlighting the dialectical process exists; now, we refer to it like environment and development. Today, mthis relationship is analyzed through sustainable development. This axiom has several theoretical views, which seeks an appropriate balance between environment and development, but also, aims to guide the progress of our society. In this article, we show its rise and definition.